Perancangan Aplikasi Pemesanan Menu Pada Rumah Makan Segar Menggunakan Model Waterfall dan Berbasis Web - Chandy Ophelia S; Siska Nurul Marwiyah; Suyanti Suyanti (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
The research in segar restaurant ordering system for analyzing the menu is still manual. This causes many problems such as the wrong order in the presentation, the wrong order with what was ordered, there is no clear record of sales every day. The results is a bad reputation for the restaurant and for the owner it will be difficult to know sales and cannot predict the food stock. So that in this research, it contains how to design a menu to simplify ordering application, speeding up the ordering process and reduce errors in the process of presenting the segar restaurant using wireless devices. The study was conducted by using field research methods which included observations and interviews as well as system development tool using UML ( unified modeling language) which consists of a usecase diagram , activity diagram and class diagram . And also using the waterfall model as a system development method, where we have to do it step by step through which we have to wait for the completion of the previous stage and run sequentially. In building this system uses 1 usecase diagram consisting of 13 descriptions usecase , 13 activity diagram and 1 class diagram. This menu ordering application built with PHP programming language and MySQL as its database . This application is designed to generate output data processing and transaction orders and sales reports